O método SLP como base para a proposição de um projeto de arranjo físico industrial: estudo de caso aplicado a uma fábrica de palmito de açaizeiro - BARROS, Guilherme Pereira (2022)
Companies in the search for greater competitiveness, aims to increasingly lean and productive processes. One of the factors that favor the efficiency of a company is how willing their physical arrangement. The main focus of this work is the analysis of the physical arrangement of palm in a factory in the city of Abaetetuba, Pará. State First definitions, objectives, importance of study of physical arrangements will be made. After the theoretical approach, a case study using the method of SLP (Systematic Layout Planning) tool used for planning and development of physical arrangements, in order to achieve maximum efficiency of the production process will be done through the rearrangement areas according to the methodology implemented. With the choice of a suitable layout, layout of equipment within the plant is facilitated and guided the maximum efficiency of operations, helping to reduce the related material handling costs and increasing productivity.